Optimizing Best-Selling Menu Production using the Linear Programming Method: Case Study on Lines Coffee - Anhar, Reisya; Haludin, Guntur; Nabila, Azra; Nareswari, Anindya; Febriana, Eka; Fadillah, Raysha; Mayadi, Muhammad; Ramadhani, Keysha (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to optimize the production of Lines Coffee to maximize profit through the application of the simplex method. Lines Coffee, a company in the food and beverage industry, features bestselling menu items such as Kopi susu gula aren, Americano, Latte, and Cappuccino. By employing the simplex method, this study seeks an optimal solution that satisfies production constraints and enhances the objective function, which is profit. The research findings indicate that the optimal solution involves producing 15 units of Americano while not producing Latte and Cappuccino. This solution yields a profit of IDR 28,000,000. Although the optimal solution suggests a focus on Americano production, Lines Coffee faces limitations in meeting market demand for Latte and Cappuccino. In conclusion, Lines Coffee may consider strategies to increase the production of Latte and Cappuccino to meet market demand. Additionally, efforts to reduce production costs could be key to further optimizing profits. This research contributes to understanding production strategies in the food and beverage industry, particularly in coffee shops.